THE COMMON AGRICULTURAL POLICY REFORM AND THE COMPETITIVNESS OF THE ROMANIAN AGRI-FOOD SECTOR - Achim, Irimescu (Economics of Agriculture, 2012)
The CAP reform, aiming for the 2014 - 2020, basically envisages maintaining the competitiveness of the European agriculture, while applying higher environmental standards and better managing of the natural resources (water, soil and air). The reform also aims at offering financial support, mainly, to the small and medium sized farms, introduces direct payments capping for the larger ones, and encourages farms to use low environmental impact technologies. The CAP budget will be frozen at the level of 2013, and thus generating competitiveness problems for the European farmers which apply higher standards (environmental protection, animal welfare, etc.) than the farmers in third countries. Romanian producers will be between the most affected farmers within the EU ones, bearing in mind the direct support they receive as a result of the new requirements/proposals. Due to the direct payments gradual increase until 2016 (phasing-in), the funds allocated to Romania will increase a lot, by over 7 billion € as comparing with the present financial programming period (2007 – 2013). Nevertheless, the Romanian producers receiving only 203€/hectar, will remain well under the current EU average for direct payments of 270€/hectar. As a result, the competitiveness of the Romanian farmers will continue to be limited, compared to their colleagues from the majority of member states who receive substantial more direct payments. Moreover, the capping will reduce the funding over a certain ceiling, thus affecting further the competitiveness of the most efficient Romanian producers.